2022
DOI: 10.1001/jamanetworkopen.2022.2983
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hearing Impairment and 24-Hour Total Movement Activity in a Representative Sample of US Adults

Abstract: IMPORTANCE Lower physical activity (PA) levels have been proposed as a mechanism to explain the association between hearing loss and various adverse outcomes of aging. But whether hearing loss is associated with lower PA is poorly understood. OBJECTIVE To evaluate whether hearing loss is associated with lower levels of PA. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional analysis was conducted in a representative sample of US adults (aged 30-69 years) who participated in the 2011-2012 cycle of the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
11
1
1
Order By: Relevance
“…Martinez-Amezcua et al have shown, however, that hearing loss is correlated with decreased movement in adults ages 30 to 69, demonstrating that this association is not exclusive to senior-age adults. 29 A few studies of smaller cohorts have also shown that hearing acuity may correlate with gait performance in both children and adults. 30,31 The findings in the present study support the notion that hearing difficulty is an important risk factor for impaired mobility for adults of all ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez-Amezcua et al have shown, however, that hearing loss is correlated with decreased movement in adults ages 30 to 69, demonstrating that this association is not exclusive to senior-age adults. 29 A few studies of smaller cohorts have also shown that hearing acuity may correlate with gait performance in both children and adults. 30,31 The findings in the present study support the notion that hearing difficulty is an important risk factor for impaired mobility for adults of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…27 Hearing loss may also contribute to social isolation, cognitive impairment, and reduced physical activity. 7,28,29 Moreover, hearing loss may disrupt auditory cues that could be important in self-perception. 32 One must also consider potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective HL was measured by 2 items from a survey questionnaire. The first of these related to troublesome hearing, with any of the following responses (a little trouble, moderate hearing trouble, a lot of trouble, or deaf) to the question, “Which statement best describes hearing without a hearing aid, personal sound amplifier, or other listening devices?” The second measure involved tinnitus by answering yes to the question, “In the past 12 months, have you been bothered by ringing, roaring, or buzzing in ears or head that lasts for 5 minutes or more?” Objective HL was measured by audiometry examinations referring to a standardized National Center for Health Statistics protocol . Air conduction thresholds were obtained at 0.5, 1, 2, 3, 4, 6, and 8 kHz in each ear using a pulsed-tone stimulus and modified Hughson-Westlake procedure across an intensity range of −10 to 120 dB hearing level .…”
Section: Methodsmentioning
confidence: 99%
“…The test was validated at a 1-kHz frequency in each ear. Consistent with prior literature, the average level was used in the final analysis . Speech-frequency HL (SFHL) pure-tone average was calculated across 4 audiometric frequencies (0.5, 1, 2, and 4 kHz) while HFHL was calculated based on 3 test frequencies (3, 4, and 6 kHz) in each ear .…”
Section: Methodsmentioning
confidence: 99%
“…Existing epidemiological studies have provided scientific evidence of the health benefits of physical activity, such as decreasing all-cause mortality, improving cognitive function, and preventing hypertension (Diaz & Shimbo 2013; Ekelund et al 2019; Jia et al 2019). Recent studies have reported a relationship between physical activity and hearing loss (Kuo et al 2021; Kawakami et al 2022; Martinez-Amezcua et al 2022). A high level of leisure physical activity is associated with a low incidence of hearing loss; an association has been established between high-intensity activities and high-frequency hearing (Kawakami et al 2022).…”
Section: Introductionmentioning
confidence: 99%